Undergraduates experiences and attitudes of writing in L1 and English - Ansarimoghaddam, Shokoufeh; Tan, Bee Hoon (Penerbit Universiti Kebangsaan Malaysia, 2014)
Writing is considered as an important language skill. Although the importance of writing is undeniably realized and highly stressed by ESL scholars, educators and instructors, most ESL tertiary students and young graduates find creating a coherent and extended piece of writing difficult and challenging. Therefore, to overcome this problem, there is a need to be aware of the students’ experiences and attitudes to writing in their first language and English language. This research is a quasi-experimental study that employs a mixed-method approach. Participants were thirty tertiary ESL students enrolled in an obligatory course in the first year of Bachelor of Arts (English) programme. The study compares participants’ writing experiences and attitudes through a questionnaire. Besides, an interview was conducted as a triangulation measure. Results suggest that participants mostly preferred using English language for various writing activities. Moreover, comparing overall items of the questionnaire revealed that the difference was not significant between the participants’ writing attitudes in their first language and English language. Furthermore, comparing each item of the questionnaire, three of them showed significant difference. Although the remaining items did not show any significant difference, most of them did receive higher mean for attitude to writing in English than first language. Participants’ interview responses disclosed the reasons. The findings of the present study can be obliging for both instructors and students to be aware of the reasons why some of the students do not like to write. Considering those reasons, instructors can help their students to improve their writing skill.